Validation and Critical Evaluation of the Effective Arterial Elastance in Critically Ill Patients. Issue 4 (April 2019) - Jozwiak, Mathieu; Millasseau, Sandrine; Richard, Christian; Monnet, Xavier; Mercado, Pablo; Dépret, François; Alphonsine, Jean-Emmanuel; Teboul, Jean-Louis; Chemla, Denis
Abstract : Objectives: First, to validate bedside estimates of effective arterial elastance = end-systolic pressure/stroke volume in critically ill patients. Second, to document the added value of effective arterial elastance, which is increasingly used as an index of left ventricular afterload. Design: Prospective study. Setting: Medical ICU. Patients: Fifty hemodynamically stable and spontaneously breathing patients equipped with a femoral ( n = 21) or radial ( n = 29) catheter were entered in a "comparison" study. Thirty ventilated patients with invasive hemodynamic monitoring (PiCCO-2; Pulsion Medical Systems, Feldkirchen, Germany), in whom fluid administration was planned were entered in a " dynamic" study. Interventions: In the "dynamic" study, data were obtained before/after a 500 mL saline administration. Measurements and Main Results: According to the "cardiocentric" view, end-systolic pressure was considered the classic index of left ventricular afterload. End-systolic pressure was calculated as 0.9 × systolic arterial pressure at the carotid, femoral, and radial artery level. In the "comparison" study, carotid tonometry allowed the calculation of the reference effective arterial elastance value (1.73 ± 0.62 mm Hg/mL). The femoral estimate of effective arterial elastance was more accurate and precise than the radial estimate. In the "dynamic" study, fluid administration increased stroke volume and end-systolic pressure, whereas effective arterial elastance (femoral estimate) and systemic vascular resistance did not change. Effective arterial elastance was related to systemic vascular resistance at baseline ( r = 0.89) and fluid-induced changes in effective arterial elastance and systemic vascular resistance were correlated ( r = 0.88). In the 15 fluid responders (cardiac index increases ≥ 15%), fluid administration increased end-systolic pressure and decreased effective arterial elastance and systemic vascular resistance (each p < 0.05). In the 15 fluid nonresponders, end-systolic pressure increased ( p < 0.05), whereas effective arterial elastance and systemic vascular resistance remained unchanged. Conclusions: In critically ill patients, effective arterial elastance may be reliably estimated at bedside (0.9 × systolic femoral pressure/stroke volume). We support the use of this validated estimate of effective arterial elastance when coupled with an index of left ventricular contractility for studying the ventricular-arterial coupling. Conversely, effective arterial elastance should not be used in isolation as an index of left ventricular afterload. Abstract : Supplemental Digital Content is available in the text.